Depression, anxiety, and type d personality in newly diagnosed breast cancer patients: a quasi-prospective association study / Beatrice Ng Andrew - Beatrice, Ng Andrew (2014)
Depression, Anxiety, and Type D Personality in Newly Diagnosed Breast Cancer Patients: A Quasi-Prospective Association Study Introduction The role of psychological factors in the development of breast cancer has been a controversial topic of discussion, due to its contradicting results ranging from no association, positive association, and even negative association. Identifying potential risk factors for breast cancer will help in the prevention of this disease. Aim This study aimed to identify if depression, anxiety trait, or Type D personality, is associated with the risk of breast cancer. The secondary objective was to identify the factors associated with depression, anxiety trait, and Type D personality among the women with newly diagnosed breast cancer. Method This was a quasi-prospective study on the new female patients who came to University Malaya Medical Centre (UMMC) Breast Clinic for any breast complaint. The participants were given the Center for Epidemiologic Studies Depression Scale, State-Trait Anxiety Inventory Form Y-2, 14-Item Type D Personality Scale, and Multidimensional Scale of Perceived Social Support self-rated questionnaires. Socio-demographic and clinical history was also obtained during the interview. Medical records were traced after one month to determine the confirmed breast disease diagnosis. Univariate and multivariate analysis was iv done for the associated factors. Prior ethical approval was obtained from the UMMC Medical Ethics Committee. Results A total of 300 patients were recruited and breast cancer was detected in 34 (11.3%) of the patients. No association was seen between depression, anxiety trait, or Type D personality, with newly diagnosed breast cancer. After multivariate analysis, only age was found to have significant positive association with subsequent diagnosis of breast cancer (p < 0.001). Depression was screened in 18 (53%) patients, and Type D personality was found in 10 (29%) of the patients with newly diagnosed breast cancer. Socio-demographic and clinical variables were not associated with depression, anxiety trait levels, or Type D personality among the newly diagnosed breast cancer patients. All the psychological variables of depression, anxiety trait, and Type D personality were found to have significant positive correlation, where depression and anxiety trait had Pearson’s r of 0.67 (p<0.001), depression and Type D personality Pearson’s r of 0.70 (p<0.001), and anxiety trait and Type D personality Pearson’s r of 0.58 (p<0.001). Conclusion This study found no significant association between depression, anxiety trait, and Type D personality with subsequent diagnosis of breast cancer. However, significant positive correlation was seen between depression, anxiety trait, and Type D personality, among those with newly diagnosed breast cancer. This positive correlation could indicate that screening for anxiety trait and Type D personality may help in identifying breast cancer patients who are more vulnerable to developing depression.